The Determinant Factors For Application Of Buying And Selling Transaction In Sharia Market - Idel Waldelmi; Afvan Aquino (International Journal of Economics, Business and Innovation Research, 2022)
The concept of sharia is currently developing and extending to the operational level of the Islamic market. The choice of models in order to improve the welfare of the ummah is limited to discourse and is gradually being implemented, making many problems to be solved. In the Ulul Albab sharia market located in Riau Province, precisely in Kampar Regency has become an example for other sharia markets. But in practice, ideal sharia transactions have not understood by interested parties namely traders, buyers and managers yet. This study uses qualitative methods through in-depth interviews to the unit of analysis, namely the manager of the Ulul Alab Islamic market, the Ulul Alabab Market Shariah Supervisory Board and strengthened by traders and buyers who transact in the Islamic market. Based on the results of the study indicate that the reason why sharia transactions that occur in the Islamic market Ulul Albab has not been optimally implemented, these are caused by four determinant factors, among others, the firstly; the factors that come from traders where traders are not all traders come from Muslim traders, there is also a background of practicing religion from traders who are still not perfect. Secondly; factors that come from consumers or buyers where buyers are not only Muslims but also non-Muslims. Heterogeneous population causes misunderstanding about the concept of sharia. The third factor, market managers do not have the operational standards of sharia policies or procedures in the Islamic market, and even the practices of usury moneylenders also operate in the Ulul Albab market. And the fourth factor is that the sharia supervisory board still does not have a clear reference in implementing the ideal sharia market practices. Therefore it is necessary to take strategic steps for market managers and the supervisory board in order to add insight through comparative studies to Islamic markets applied in Indonesia in order to obtain the concept of sharia transactions that are by heterogeneous community cultures.